PENGARUH RISIKO KREDIT, RISIKO LIKUIDITAS, DAN KECUKUPAN MODAL TERHADAP KINERJA KEUANGAN PERBANKAN SEBELUM DAN PADA MASA PANDEMI COVID – 19 (Studi pada Perbankan Konvensional Go Public yang Tedaftar pada Bursa Efek Indonesia Periode 2017-2021) - Thania Putri Arini; Sparta Sparta (Journal of Accounting, Management and Islamic Economics, 2023)
The purpose of this research is to examine, analyze, and compare how the influence of Credit Risk, Liquidity Risk, and Capital Adequacy on Banking Financial Performance Before and During the Covid-19 Pandemic by using a sample in Go Public Conventional Banking for the 2017-2021 period. This study uses a purposive sampling technique so that 42 banks are used as research samples. The independent variable Credit Risk is measured using the NPL ratio (Non Performing Loan), Liquidity Risk is measured using the LDR ratio (Loan to Deposit Ratio), and Capital Adequacy is measured using the CAR (Capital Adequacy Ratio) ratio. For the dependent variable, namely Banking Financial Performance, it is measured using the ROA (Return On Asset) ratio. The results of this study state that prior to the pandemic, Credit Risk had a significant negative effect on the Financial Performance of the Bank, while for Liquidity Risk and Capital Adequacy it had a significant positive effect on the Financial Performance of the Bank. After the Pandemic, the results stated that Credit Risk still had a significant negative effect on Banking Financial Performance, Liquidity Risk still had a significant positive effect on Banking Financial Performance, but for Capital Adequacy it did not have a significant effect on Financial Performance.